Synthesis and Characterization of Di(Alkoxy) Tripseudohalido-Tungsten(V) - Dabas, P.; Saxena, R.; Rastogi, M.K. (Asian Journal of Chemistry, 2010)
Pseudohalide derivatives of the type (RO)2W(Ps)3 of (RO)2WCl3 have been synthesized by the interaction of (RO)2WCl3 with potassium pseudohalides (Ps = thiocyanate, cyanate and azide) in tetrahydrofuran ( R = Me, Et, i-Pr, n-Bu, i-Bu and t-Bu). The derivatives have been characterized by their elemental analysis, IR spectra and other physical measurements. It has been observed that the pseudohalide groups are attached to the tungsten atom through the atom with lesser electronegativity in the group.